Efecto del cambio de uso del suelo de páramo a cultivo y pasto sobre fracciones orgánicas en la microcuenca Sicalpa - Castro Castillo, Joselyn Gabriela (2023)
The changes in the practices of use and management of soil alter its CO intake as well as the dynamic and the balance level of CO in the soil. The changes produced by the soil management practices could be predicted considering the more sensible fractional changes, which are obtained in the first short periods. The objective of this work was to evaluate the impact of the changes from moorland to pasture and crop over the labile and stable CO fractions. Three kinds of soil were analyzed: moorland, pasture, and monocrops. In each situation, 10 samples from 0 to 30 cm were taken. It was determined: thick articulated CO (COPg, 105-2000 μm), thin articulated CO (COPf, 53-105 μm) and CO associated with mineral matter (COM, 0-53 μm). In addition, It was also performed pH and melanic index analysis, NaF test, bulk density, and total organic matter. The highest COPg content was registered in moorland soil (128,43 gC/kg) and the lowest value was in crop soil (106,87 gC/kg). The replacement from the moorland to the crop caused a decrease of COPg at 21,56gC/kg approximately. Similarly, the way the content of COPg in low pasture soil (105,12 gC/kg) decreased when it was replaced with normal pasture soil by 150gC/kg leading to a loss of 23,31 gC/kg. The highest economical value found was related to moorland because of its capacity to store carbon, showing that moorland areas play a strategic role in carbon storage providing an ecosystem service of carbon sequestration.